A molecular engineering toolbox for the structural biologist. (2nd May 2017) - Debelouchina, Galia T.; Muir, Tom W.
Abstract: Exciting new technological developments have pushed the boundaries of structural biology, and have enabled studies of biological macromolecules and assemblies that would have been unthinkable not long ago. Yet, the enhanced capabilities of structural biologists to pry into the complex molecular world have also placed new demands on the abilities of protein engineers to reproduce this complexity into the test tube. With this challenge in mind, we review the contents of the modern molecular engineering toolbox that allow the manipulation of proteins in a site-specific and chemically well-defined fashion. Thus, we cover concepts related to the modification of cysteines and other natural amino acids, native chemical ligation, intein and sortase-based approaches, amber suppression, as well as chemical and enzymatic bio-conjugation strategies. We also describe how these tools can be used to aid methodology development in X-ray crystallography, nuclear magnetic resonance, cryo-electron microscopy and in the studies of dynamic interactions. It is our hope that this monograph will inspire structural biologists and protein engineers alike to apply these tools to novel systems, and to enhance and broaden their scope to meet the outstanding challenges in understanding the molecular basis of cellular processes and disease.